PENGARUH PENDEKATAN KONTEKSTUAL BERBANTUAN MEDIA COPER PADA MATERI PERBANDINGAN TERHADAP KEMAMPUAN1PEMAHAMAN MATEMATIS DAN MOTIVASI1BELAJAR SISWA - Herdiansyah, Mohamad; Iswara, Prana Dwija; Isrok'atun, I. (Jurnal Pena Ilmiah, 2017)
The research placed at V grade at comparison material. Population of this research is whole of elementary school in Paseh Subdistrict, Sumedang, then the sample of population is Cijambe 2 elementary school as exsperiment class and Sidaraja elementary school as control class. The goals of this research is to knowing the effect from contextual approach with coper media support to mathematical understanding ability and study motivation, and for knowing rhe correlation between mathematical understanding ability with study motivation. This research use experiment method that compared the experiment class with control class, which have different treatment. Based on the data, it describe that contextual approach with coper media support could give more effect to mathematical understanding ability, meanwhile at study motivation contextual approach with coper media support can’t give more effect. Then, we can know that mathematical understanding ability and study motivation have strong correlation.